Evaluation of pharmaceutical concerns in Germany: frequency and potential reasons - Gradl G; Krieg EM; Schulz M (Centro de Investigaciones y Publicaciones Farmaceuticas, 2016)
Background: Generic substitution can have unintended consequences. In Germany, brand name to generic or generic to generic switching is mainly driven by rebate contracts. Frequent switching may raise concerns about bio- and therapeutic equivalence. Expected patient confusion may result in compromised medication adherence or new onset of other drug-related problems. Since 2008, pharmacists are allowed to deviate from rebate contracts by denying substitution due to pharmaceutical concerns on an individual basis. Objectives: To explore the frequency of documented pharmaceutical concerns in Germany between July 2011 and December 2013 and to identify the medicines most frequently related to pharmaceutical concerns in 2013. Methods: We analyzed documented pharmaceutical concerns in all prescribed drugs at the expense of any statutory health insurance company requiring pharmacies' generic substitution according to rebate contracts. Results: Since July 2011, the frequency of documented pharmaceutical concerns in relation to prescribed drug products with rebate contracts requiring substitution increased consistently and doubled between July 2011 and July 2013. Overall in 2013, the trend of the two previous years continued and reached approximately 1.5%. The most affected drugs/drug classes were thyroid hormones (in particular combinations with iodide; 15.9%) followed by ondansetron (12.5%), and levothyroxine (11.3%). For all drugs/drug classes under investigation, product-, patient- or disease-related aspects could be identified which are potential reasons to deny substitution and to document pharmaceutical concerns. Conclusions: Although there is no electronic recording of the specific reasons for pharmaceutical concerns in claims data, our analyses support the assumption that pharmacists make use of this instrument based on individual clinical decisions and as required by contract. Pharmaceutical concerns are, therefore, an important instrument for pharmacies to refuse generic substitution. They are considered to prevent compromised medication safety and to assure pharmacotherapy effectiveness in a generic substitution environment driven by low drug prizes above all.